ANALISIS PERLINDUNGAN ANAK KORBAN KEKERASAN OLEH PEMERINTAH DAERAH PROVINSI RIAU - Andriyus, Andriyus (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2021)
Violence against children continues to increase and the most concerning is sexual violence. One of the province which gets the spotlight due to the high number of violence against children is the province of Riau. This study aims to analyze the protection of child victims of violence by the Regional Government of Riau Province as well as to determine the barriers Government Regional Province of Riau in giving protection to child victims of violence such. Type research survey descriptive by using the method of qualitative.Research informants are determined according to their authority and research needs to answer problems through data collection observation, interview, and documentation. The concept of theory that is used is the concept Prinst of protection specifically for children who become victims of acts of crime with indicators Efforts rehabilitation, both within the institution and outside the institution, Effort protection of the preaching of identity through the media mass and to avoid labeling, Giving assurance of safety for witnesses of victims and witnesses experts, both physically, mentally, and socially, and Providing accessibility to obtain information regarding case developments. The results of the study indicate that the Government of the Province of Riau already provide protection to child victims of violence by way of doing advocacy, protection, counseling, monitoring, and recovery after trauma. Then the government provides aid law and advocacy law to the victim at the time of the trial and the victims are also given access to information that is widest on the development of the case in court. The factors inhibiting the Government of the Regional Province of Riau in giving protection to child victims of violence is the lack of a source of power of man and awareness of the public in reporting events of violence against children either as victims or as witnesses.